ERA-CRISPR/Cas12a system: a rapid, highly sensitive and specific assay for Mycobacterium tuberculosis - Gan, Tian; Yu, Jianwei; Deng, Zhongliang; He, Jun (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionMycobacterium tuberculosis, the causative agent of human tuberculosis, poses a significant threat to global public health and imposes a considerable burden on the economy. However, existing laboratory diagnostic methods for M. tuberculosis are time-consuming and have limited sensitivity levels.MethodsThe CRISPR/Cas system, commonly known as the “gene scissors”, demonstrates remarkable specificity and efficient signal amplification capabilities. Enzymatic recombinase amplification (ERA) was utilized to rapidly amplify trace DNA fragments at a consistent temperature without relying on thermal cyclers. By integrating of CRISPR/Cas12a with ERA, we successfully developed an ERA-CRISPR/Cas12a detection system that enables rapid identification of M. tuberculosis.ResultsThe sensitivity of the ERA-CRISPR/Cas12a fluorescence and lateral flow systems was 9 copies/μL and 90 copies/μL, respectively. Simultaneously, the detection system exhibited no cross-reactivity with various of respiratory pathogens and non-tuberculosis mycobacteria, demonstrating a specificity of 100%. The positive concordance rate between the ERA-CRISPR/Cas12a fluorescence system and commercial qPCR was 100% in 60 clinical samples. Meanwhile, the lateral flow system showed a positive concordance rate of 93.8% when compared to commercial qPCR. Both methods demonstrated a negative concordance rate of 100%, and the test results can be obtained in 50 min at the earliest.DiscussionThe ERA-CRISPR/Cas12a system offers a rapid, sensitive, and specific method that presents a novel approach to laboratory diagnosis of M. tuberculosis.